ANALYSIS OF ORE DELIVERY COSTS DEPENDING ON THE PRODUCTIVITY OF VARIOUS TYPES OF LOAD-HAUL-DUMP MACHINES - Yehorchenko R. R. (НТУ «ДП», 2025)
The effectiveness of extraction operations and the comprehensive quantitative and qualitative recovery of ore reserves are critical issues in the development of high-grade iron ore through sublevel caving systems in Kryvbas mines. A primary technological process in this system is ore release through horizontal bottom drifts of the receiving levels. Ore transportation is a crucial component of the extraction process, determining the efficiency of ore release and overall mining productivity. The selection of transportation equipment significantly impacts the organization of work and the productivity of the entire block. In modern underground ore deposit extraction systems, ore release and transportation are among the most labor-intensive and inefficient processes. The release of fragmented ore from the extraction area is typically carried out from under caved surrounding rock or through a network of specialized drifts uniformly distributed beneath the extraction face. The ore moves through the extraction area and release drifts under the influence of gravity.
Keywords: effectiveness; extraction operations